STUDI RINGKAS PEMEROLEHAN BAHASA PADA ANAK - Salamah, Siti (Universitas Ahmad Dahlan, 2015)
Language acquisition is an important part of a persons life. Language is a means of communication and social interaction that must be mastered an early by someone. Good capability in an early language mastery will support the quality of human life, especially in the social interaction aspect . Considering the importance of early language acquisition, child language acquisition is importance to be studied. This paper is presents a brief overview of language acquisition in terms of the ways and the stages of language acquisition in children. Furthermore, this paper is also presents the design and research methods into language acquisition.